A Novel Human Membrane Protein Interacting with the Short Fiber of Enteric Adenovirus. (9th December 2012) - Favier, Anne-Laure; Grzela, Renata; Tcherniuk, Siergiej; Harsi, Marianna Charlotte; Chroboczek, Jadwiga
Abstract : Human enteric adenoviruses of species F, HAdV-40 and HAdV-41 (Ad40 and Ad41), are associated with gastroenteritis in children. Ad attachment to the primary receptor on the cell surface is mediated by the distal head domain of the fiber protein, an antenna-like component of the adenovirus capsid. Differently from the majority of human Ads that possess one type of fiber on their capsid, the Ad40 and 41 have two distinct fibers. The long fiber recognizes the host membrane protein CAR, which permits virus attachment, but nothing is known about the role of the short fiber. Using the head domain of the Ad41 short fiber, we fished out a putative membrane protein that has never been previously described. This partner of the short fiber of enteric Ad41 (ParAd41) is a small, hydrophobic protein with three putative trans membrane domains, which interacts with the Ad41 short fiber but not with the Ad41 long fiber or with the fiber of respiratory Ad2 serotype. ParAd41 is localized in intracellular membranes including the nuclear membrane. Saturation of the short fiber with ParAd41 inhibits virus infectivity, which substantiates the putative role of ParAd41 in enteric Ads tropism. It is conceivable that the interaction of the short fiber with ParAd41 mediates virus postattachment endocytosis step as well as interaction with the nuclear membrane prior to the injection of viral DNA into the nucleus, thus enabling enteric adenovirus infection. This study is the first one to probe the molecular nature of enteric Ad41 tropism.